2012
DOI: 10.1016/j.ijrobp.2011.06.1961
|View full text |Cite
|
Sign up to set email alerts
|

Dose Constraints to Prevent Radiation-Induced Brachial Plexopathy in Patients Treated for Lung Cancer

Abstract: Purpose As the recommended radiation dose for non-small cell lung cancer (NSCLC) increases, meeting dose constraints for critical structures like the brachial plexus becomes increasingly challenging, particularly for tumors in the superior sulcus. In this retrospective analysis, we compared dose-volume histogram information with the incidence of plexopathy to establish the maximum tolerated dose to the brachial plexus. Methods and Materials We identified 90 patients with NSCLC treated with definitive chemora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…It has been suggested that a range exists from a two-fold effect to higher [12,13]. More recently dose constraints from Amini et al [14] showed that patients treated for superior sulcus lung cancers with definitive CRT require that a median dose to the BP be kept below 69Gy and the maximum dose to 2 cc below 75Gy to prevent brachial plexopathy. We found no significant difference in the risk of brachial plexopathy for patients treated with or without CRT although most of our patients were treated with CRT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a range exists from a two-fold effect to higher [12,13]. More recently dose constraints from Amini et al [14] showed that patients treated for superior sulcus lung cancers with definitive CRT require that a median dose to the BP be kept below 69Gy and the maximum dose to 2 cc below 75Gy to prevent brachial plexopathy. We found no significant difference in the risk of brachial plexopathy for patients treated with or without CRT although most of our patients were treated with CRT.…”
Section: Discussionmentioning
confidence: 99%
“…The time to the appearance of symptoms may vary significantly. Recent modern studies have reported median times to onset of symptoms ranging from 6.5 months to 4 years from the completion of radiotherapy and ranges of 1.4 months to 26 years [2,3]. Once they develop, there may be a gradual evolution of symptoms or a more rapid progression with time, which may on occasion culminate in complete loss of function of the affected arm [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment options for these patients remain inadequate, and prognosis is poor. Brachial plexopathy has been associated with greater cumulative radiation dose to the brachial plexus (BP), radiotherapy fraction size, maximum dose, as well as the addition of chemotherapy and neck dissection [1,2,4-6]. One group recently used a validated symptom questionnaire in order to screen a large head-and-neck cancer population who had undergone radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The time to the appearance of symptoms may vary significantly. Recent modern studies have reported median times to onset of symptoms ranging from 6.5 months to 4 years from the completion of radiotherapy and ranges of 1.4 months to 26 years [2,3]. Once they develop, there may be a gradual evolution of symptoms or a more rapid progression with time, which may on occasion culminate in complete loss of function of the affected arm [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment options for these patients remain inadequate, and prognosis is poor. Brachial plexopathy has been associated with greater cumulative radiation dose to the brachial plexus (BP), radiotherapy fraction size, maximum dose, as well as the addition of chemotherapy and neck dissection [1,2,[4][5][6]. One group recently used a validated symptom questionnaire in order to screen a large head-and-neck cancer population who had undergone radiation therapy.…”
Section: Introductionmentioning
confidence: 99%